“Can’t Use Old Keys to Open New Doors”: Relational Desistance Mechanisms Within Community Violence Interventions - Peter Simonsson PhD, MSW, LCSW; Caterina Gouvis-Roman PhD; Shadd Maruna PhD; Peter Twigg MA (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Community Violence Intervention (CVI) programs show promising results in reducing health disparities such as firearm injury and violence. However, the process by which these programs bring about positive change is less well due to program variations and the focus of existing studies. Hence, program components and strategies used in day-to-day community violence intervention work are less clear. To address this gap, this study used in-depth interview data focused on understanding the early engagement of participants in an east coast United States community violence intervention program (n = 32). Questions focused on the process by which credible messengers as outreach workers motivate at-risk individuals to join the program, obtaining descriptions of the personal mentoring and cognitive change efforts driving desistance. Three key themes emerged: outreach workers use their own “lived experience” or self-narratives to build trust and motivate at-risk individuals to join and stick with programing; outreach workers and participants form a unique relationship through which participants are buoyed by belonging to a new “family”; and participants acquire new skills and prosocial peer networks that help them navigate away from the streets. Together, these processes support at-risk individuals through what might be best understood as a social movement as opposed to an individualistic process of “corrections” or reform.